ELECTROCHEMICAL TRANSFORMATION OF CAPTURED CARBON DIOXIDE INTO SUSTAINABLE FUELS AND CHEMICALS: LEVERAGING KC8 TECHNOLOGY FOR ADVANCED CO₂ CAPTURE AND UTILIZATION - Neelam Shahadat; Md Mojahidul Islam; Muhammad Iqbal Tabssum; Shaheena Anjum; Komal Tanveer; M Ahmad; Muhammad Hawaisa Masood; Aleeza Husnain (Spectrum of Engineering Sciences, 2025)
The rapid increase in atmospheric carbon dioxide (CO₂) concentrations due to anthropogenic activities is a major contributor to climate change and environmental degradation, prompting urgent efforts to develop efficient carbon capture and utilization (CCU) technologies. This research investigates a pioneering integrated system that combines the novel use of potassium graphite (KC8) for highly effective CO₂ capture with an advanced electrochemical conversion process to synthesize sustainable fuels and valuable chemicals. KC8, with its exceptional electron-donating properties and strong chemical affinity for CO₂, enables efficient and selective carbon capture at ambient temperatures and pressures, overcoming many of the limitations faced by traditional carbon capture materials. Once captured, the CO₂ is electrochemically reduced in a specialized reactor designed to optimize reaction kinetics and product selectivity, leading to the generation of critical renewable energy carriers such as syngas, formic acid, and methanol. Experimental results demonstrate that the KC8-assisted capture significantly enhances the Faradaic efficiency of the electrochemical process, lowers the overall energy input required for CO₂ conversion, and improves the selectivity toward desired fuel and chemical products compared to conventional electrolysis systems. This dual-stage approach not only provides a viable method for mitigating greenhouse gas emissions but also promotes a circular carbon economy by transforming captured CO₂, a major environmental pollutant, into commercially viable and environmentally friendly products. The findings indicate that the integration of KC8 capture technology with electrochemical conversion presents a scalable, cost-effective, and energy-efficient pathway toward sustainable carbon management and renewable fuel production. Furthermore, this approach aligns with global efforts to achieve net-zero emissions targets and offers a promising platform for future research in the field of sustainable energy and environmental technology. The study contributes valuable insights into the design of next-generation CCU systems and highlights the critical role of advanced materials in enabling efficient electrochemical CO₂ utilization for climate mitigation and green chemistry.